2014
DOI: 10.1590/0074-0276130469
|View full text |Cite
|
Sign up to set email alerts
|

In house reverse membrane hybridisation assay versus GenoType MTBDRplus and their performance to detect mutations in the genes rpoB, katG and inhA

Abstract: Drug-resistant tuberculosis (TB) threatens global TB control and is a major public health concern in several countries. We therefore developed a multiplex assay (LINE-TB/MDR) that is able to identify the most frequent mutations related to rifampicin (RMP) and isoniazid (INH) resistance. The assay is based on multiplex polymerase chain reaction, membrane hybridisation and colorimetric detection targeting of rpoB and katG genes, as well as the inhA promoter, which are all known to carry specific mutations associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
(52 reference statements)
0
3
0
1
Order By: Relevance
“…Felkel et al [18] reported four false positive results and a false negative one when comparing them with cultures of patients without a history of MTBC treatment. Ferreira Junior et al [27] reported that the GenoType MTBDRplus identified two out of 40 (5%) INH resistant and three out of 40 (7.5%) RIF resistant strains as sensitive. In the study reported by Gu et al [20], with this assay, one out of six (16.6%) RIF resistant strains and one out of seven (14.2%) INH resistant strains were falsely detected as sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…Felkel et al [18] reported four false positive results and a false negative one when comparing them with cultures of patients without a history of MTBC treatment. Ferreira Junior et al [27] reported that the GenoType MTBDRplus identified two out of 40 (5%) INH resistant and three out of 40 (7.5%) RIF resistant strains as sensitive. In the study reported by Gu et al [20], with this assay, one out of six (16.6%) RIF resistant strains and one out of seven (14.2%) INH resistant strains were falsely detected as sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…Genotype® MTBDRplus has been compared to phenotypic and other molecular assays with very impressive performance and was endorsed by WHO for MDR-TB molecular detection in 2008 ( Nikolayevsky et al 2009 , Ferreira Jr et al 2014 , Asante-Poku et al 2015 ). Since the first report using MLPA as a promising alternative for TB genetic characterisation ( Bergval et al 2008 ), few studies evaluating MLPA in comparison to other assays have been described ( Bergval et al 2012 , Sengstake et al 2014 , Chaidir et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Target genes of both drugs were amplified as described elsewhere by Junior et al (2014) [16] and submitted to DNA sequencing using Big Dye® Kit Terminator Cycle Sequencing (Applied Biosystems, Foster City, CA, USA). Capillary electrophoresis was performed with an automated genetic analyzer ABI Prism 3130xl (Applied Biosystems), following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%